Crystallization-induced emission enhancement of highly electron-deficient dicyanomethylene-bridged triarylboranes. Issue 64 (20th July 2021) - Liao, Guanming; Zhang, Jia; Zheng, Xiaoyan; Jia, Xiaodi; Xu, Jialiang; Zhao, Fenggui; Wang, Nan; Liu, Kanglei; Chen, Pangkuan; Yin, Xiaodong
Abstract : A dicyanomethylene-bridged triarylborane with highly electron-deficient character exhibits crystallization-induced emission enhancement which can be assigned to a tight molecular stacking mode. Abstract : A highly electron-deficient dicyanomethylene-bridged triarylborane, F MesB-TCN, was reported with a low-lying LUMO and crystallization-induced emission enhancement in its block-shape crystal. DFT calculations revealed lower re-organization energy of the block crystal than that of the weakly emissive acicular crystal. This work explored a novel boron-containing skeleton with interesting optical properties.